An epigenetic hypothesis of aging-related cognitive dysfunction - Penner, Marsha R.; Roth, Tania L.; Barnes, Carol; Sweatt, David (Frontiers in Aging Neuroscience, 2010)
This brief review will focus on a new hypothesis for the role of epigenetic mechanisms in aging-related disruptions of synaptic plasticity and memory. Epigenetics refers to a set of potentially self-perpetuating, covalent modifications of DNA and post-translational modifications of nuclear proteins that produce lasting alterations in chromatin structure. These mechanisms, in turn, result in alterations in specific patterns of gene expression. Aging-related memory decline is manifest prominently in declarative/episodic memory and working memory, memory modalities anatomically based largely in the hippocampus and prefrontal cortex, respectively. The neurobiological underpinnings of age-related memory deficits include aberrant changes in gene transcription that ultimately affect the ability of the aged brain to be “plastic”. The molecular mechanisms underlying these changes in gene transcription are not currently known, but recent work points toward a potential novel mechanism, dysregulation of epigenetic mechanisms. This has led us to hypothesize that dysregulation of epigenetic control mechanisms and aberrant epigenetic “marks” drive aging-related cognitive dysfunction. Here we focus on this theme, reviewing current knowledge concerning epigenetic molecular mechanisms, as well as recent results suggesting disruption of plasticity and memory formation during aging. Finally, several open questions will be discussed that we believe will fuel experimental discovery.